TP53 status regulates ACSL5-induced expression of mitochondrial mortalin in enterocytes and colorectal adenocarcinomas - Klaus, Christina; Schnölzer, Martina; Kopitz, Jürgen (Cell & tissue research, 2014)
Acyl-CoA synthetase 5 (ACSL5), a mitochondrially localized enzyme, catalyzes the synthesis of long-chain fatty acid thioesters and is physiologically involved in pro-apoptotic sensing of enterocytes. The aim of the present study is to identify an ACSL5-dependent regulation of mitochondrially expressed proteins and the characterization of related pathways in normal and diseased human intestinal mucosa. Proteomics of isolated mitochondria from ACSL5 transfectants and CaCo2 controls were performed. ACSL5-dependent protein synthesis was verified with quantitative reverse transcription plus the polymerase chain reaction, Western blotting, short-interfering-RNA-mediated gene silencing and additional cell culture experiments. Lipid changes were analyzed with tandem mass spectrometry. ACSL5-related pathways were characterized in normal mucosa and sporadic adenocarcinomas of the human intestine. In CaCo2 cells transfected with ACSL5, mortalin (HSPA9) was about two-fold increased in mitochondria, whereas cytoplasmic mortalin levels were unchanged. Disturbance of acyl-CoA/sphingolipid metabolism, induced by ACSL5 over-expression, was characterized as crucial. ACSL5-related over-expression of mitochondrial mortalin was found in HEK293 and Lovo (wild-type TP53 [tumor protein p53]) and CaCo2 (p53-negative; TP53 mutated) cells but not in Colo320DM cells (mutated TP53). In normal human intestinal mucosa, an increasing gradient of both ACSL5 and mortalin from bottom to top was observed, whereas p53 (wild-type TP53) decreased. In sporadic intestinal adenocarcinomas with strong p53 immunostaining (mutated TP53), ACSL5-related mortalin expression was heterogeneous. ACSL5-induced mitochondrial mortalin expression is assumed to be a stress response to ACSL5-related changes in lipid metabolism and is regulated by the TP53 status. Uncoupling of ACSL5 and mitochondrial mortalin by mutated TP53 could be important in colorectal carcinogenesis.